Design and Fabrication of a Novel Wideband DNG Metamaterial with the Absorber Application in Microwave X-Band - Ahmed Mahmood; Gölge Ögücü Yetkin; Cumali Sabah (Advances in Condensed Matter Physics)
A novel metamaterial, which exhibits a wideband double negative behavior in X-band, is proposed, designed, and investigated in this paper. The metamaterial is composed of modified S-shaped split-ring resonators (S-SRR). The periodic structure is designed and simulated using CST MWs. Next, the experiments are carried out, and it is shown that the simulation and the experimental results agree well and the designed structure has a wide bandwidth in X-band. An absorber application of this metamaterial is also provided, and the structure can be used as an absorber with absorption rate of over 80% for the polarization angles between 0° and 40°.